Documents on the papal plenary indulgences 1300-1517 preached in the Regnum Teutonicum - Jenks, Stuart (Later Medieval Europe, 2018)
Chapter 21. Indulgence for the Hospital of the Holy Spirit in Rome 1514/18Chapter 22. Indulgence in Aid of the Dominicans of Augsburg 1514/17; Chapter 23. Indulgence for the Cathedral of Trier 1515/16; Chapter 24. Indulgence for the Repair of the Dikes in the Burgundian Netherlands 1515/18; Chapter 25. Indulgence in Aid of the Reconstruction of the Parish Church of Brüx/Most 1516/18; Chapter 26. St Peter Indulgence 1514/18; Chapter 27. St Peter Indulgence 1516/18; Conclusion; The Cost of the Spiritual Benefits of Plenary Indulgences; How Burdensome were the Fees?